Ecofriendly dyeing of silk fabric with yellow natural and synthetic dye - Hamid Ali Tanveer; Shahid Adeel; Fazal-ur-Rehman; Muhammad Ibrahim; Al Mojnun Shamim; Muhammad Aftab; Muhammad Imran; Rony Mia (Results in Engineering)
The utilization of advanced technologies in isolation of natural products and the application of synthetic dyes is gaining worldwide attention for their eco-friendly and cost-effective nature. This study explores the use of microwave (MW) technology to modify the dyeing behaviour of yellow natural (turmeric extract) and synthetic (Acid Yellow 36) dye colorants on silk fabric. The significance of this research lies in its contribution to sustainable textile processing by comparing the effectiveness of natural and synthetic dyes using an innovative heating method. MW treatment of up to 2–10 min was used to stimulate the dye solution and fabric, with dyeing variables were selected using statistical modelling. For the natural dye from curcumin rhizome, mordanting was performed before and after dyeing. The shades made using optimized conditions were assessed as per ISO standards for colourfastness. The study's novelty arises from its comparative analysis of natural and synthetic dyes subjected to microwave-assisted heating technology. Key findings indicated that MW treatment holds significant potential to alter fabric surfaces, improving their interaction with dyes. Furthermore, the utilization of eco-chemicals in natural dyeing has rendered the process more sustainable. Therefore, this study advances sustainable textile dyeing by illustrating the efficacy of microwave-assisted heating in enhancing dye absorption and colorfastness for natural and synthetic dyes on silk fabric, potentially decreasing energy usage and processing duration in textile coloration.